Malondialdehyde in Exhaled Breath Condensate as a Marker of Oxidative Stress in Different Pulmonary Diseases - Bartoli, M. L. (Hindawi Publishing Corporation, 2011)
Background. Oxidative stress plays a role in the pathogenesis of many chronic inflammatory lung diseases. Exhaled breath condensate (EBC) collection is a noninvasive method to investigate pulmonary oxidative stress biomarkers such as malondialdehyde (MDA). Subjects and Methods. We measured MDA levels in EBC in a large number of patients (N = 194) with respiratory diseases: asthma (N = 64), bronchiectasis (BE, N = 19), chronic obstructive pulmonary disease (COPD, N = 73), idiopathic pulmonary fibrosis (IPF, N = 38). Fourteen healthy nonsmoking subjects were included as controls. Results. Excluding IPF subjects, MDA levels were significantly higher in all disease groups than in control group. MDA was significantly higher in COPD than asthmatic and BE subjects. Among asthmatics, corticosteroids-treated subjects had lower MDA levels than untreated subjects. COPD subjects showed an inverse correlation between MDA concentrations and FEV(1)% (rho:  −0.24, P < .05). Conclusions. EBC-MDA is increased in subjects with chronic airway disorders, particularly in COPD, and it is related to FEV(1) reduction.